2020
DOI: 10.1177/0033294120968086
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Emotion Regulation and Psychological Distress: What Is the function of Negative Mood Regulation Expectancies in This Relationship?

Abstract: Individuals’ tendency to use their interactions with others in the management of their own emotions is called Interpersonal Emotion Regulation (IER). Limited studies have explored the association between IER and psychological distress with none focusing on the role of mediating variables in this relationship. The current study aims to explore the role of negative mood regulation expectancies (NMRE), which is defined as one’s confidence in the effectiveness of their coping skills while dealing with difficult em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(69 reference statements)
2
4
0
Order By: Relevance
“…The indirect associations of perspective-taking and social modeling with social anxiety through NMRE were not significant. A similar pattern of results was documented in a study conducted by Ray-Yol and Altan-Atalay ( 2020 ), which reported that NMRE did not significantly mediate the relationship between IER strategies and psychological distress except for soothing. Ray-Yol and Altan-Atalay ( 2020 ) argued that both perspective-taking and social modeling may potentially provide individuals an opportunity to acquire emotion regulation skills.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The indirect associations of perspective-taking and social modeling with social anxiety through NMRE were not significant. A similar pattern of results was documented in a study conducted by Ray-Yol and Altan-Atalay ( 2020 ), which reported that NMRE did not significantly mediate the relationship between IER strategies and psychological distress except for soothing. Ray-Yol and Altan-Atalay ( 2020 ) argued that both perspective-taking and social modeling may potentially provide individuals an opportunity to acquire emotion regulation skills.…”
Section: Discussionsupporting
confidence: 86%
“…A similar pattern of results was documented in a study conducted by Ray-Yol and Altan-Atalay ( 2020 ), which reported that NMRE did not significantly mediate the relationship between IER strategies and psychological distress except for soothing. Ray-Yol and Altan-Atalay ( 2020 ) argued that both perspective-taking and social modeling may potentially provide individuals an opportunity to acquire emotion regulation skills. In other words, when one experiences a stressful situation, approaching others to get their opinion (perspective taking) and observing others to learn how they cope with negative feelings (social modeling) may not undermine one’s expectancies of own coping skills.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Limited studies have investigated the relationship between IER and stress, and no one has addressed the role of mediators in this relationship. Current research is aimed at exploring the role of the prospective cognitive test, which is defined as an individual's confidence in the effectiveness of his or her cognitive skills when combined with difficult emotions [ 6 ]. Stress is one of the psychological reactions that accompany users.…”
Section: Related Workmentioning
confidence: 99%
“…Depression has been described as an "autoregulatory disorder", perhaps more accurately described as an "inability to care for others" [8][9][10]. This "capacity to care for others" actually refers to the emotional capacity.…”
Section: Introductionmentioning
confidence: 99%